Peran Teknologi Pendidikan dalam Perspektif Merdeka Belajar di Era 4.0 - aan widiyono; Izzah Millati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2021)
This study aims to describe the role of educational technology in perspective freedom to learn in the 4.0 era. The research implementation is about how teachers understand the concept of freedom to learn in applying educational technology as the basis for learning in the 4.0 era. The program was designed to improve students' literacy and numeracy skills following Indonesia's subpar achievement in the global education assessment, PISA. The research method uses descriptive analysis techniques with literature review. The research results explain that educational technology a very important in freedom to learn program in the era 4.0 thus improving the quality of education. This condition can be seen from the implementation of the main policy on freedom of learning which provides freedom to innovate and freedom to learn independently for schools, teachers, and students. Keywords: Educational Technology, Freedom to Learn, Era 4.0,